The assimilation of augmented reality in learning environment / Amirul Afif Zambri and Muhamad Fairus Kamaruzaman - Zambri, Amirul Afif; Kamaruzaman, Muhamad Fairus (Universiti Teknologi MARA, 2020)
The pandemic Covid-19 has led the Malaysia Government to execute the Movement Control Order (MCO) in which resulted in the closings of all schools. Due to this matter, to furnish all the student learning needs. The learning paradigm has to shift from a face-to-face approach to a non-face to face approach. The Ministry of Education (MOE), Malaysia recommends all schools under MOE to use Open Distance Learning (ODL) which is part of the e-learning process. The advancement of the Internet of Things (IoT) and the integration of technology know-how, will make every aspect of learning possible. This study goes some way to bridging the gap by exploring students' engagement and motivation towards Augmented Reality (AR). Findings showed encouraging learning outcomes as quantified by data analysis. This unique feature of Augmented Reality had led it to be implemented in education as it can convey abstract knowledge to a comprehensible context. Augmented Reality provides a fascinating learning environment as it increases the motivation and attractiveness of teaching and learning in real-life scenarios for students.